THE INFLUENCE OF SHARIA MARKETING TOWARDS SATISFACTION OF CUSTOMERS OF PURCHASE DECISIONS AS A MEDIATION VARIABLE (A STUDY ON SOFIE LOCAL FOOD IN PALU CITY) - Sasnita, Afriyani; Dg. Parani, Syamsul Bahri; Ponirin, Ponirin (Master of Management Study Program, Faculty of Economics and Business, Tadulako University, 2021)
This research aims to find out the influence of sharia marketing which consists of sharia products, sharia prices, sharia places, and sharia promotions towards customers' satisfaction of purchase decisions as a mediation variable at Sofie local food in Palu City. There were 96 respondents of customers at Sofie local food in Palu City involved in the research sample through the purposive sampling technique. Data were analyzed using SEM analysis assisted by the SmartPLS3 application. The results of the research show that sharia marketing has a significant influence directly towards customers’ satisfaction, sharia marketing has a significant influence on purchasing decisions, and purchasing decisions have a significant influence on customers’ satisfaction. While customers’ satisfaction indirectly has a significant influence through purchasing decisions, namely sharia products, sharia prices, and sharia places, the sharia promotion indirectly does not have a significant influence towards customers’ satisfaction of purchasing decisions. Keywords: Sharia Marketing, Customers’ Satisfaction, Customers’ Decision